The Role of Accountability in Establishing a Welfare State: A Research Analysis in the Context of the Caliphate of Hazrat Umar Farooq - Sangi, Khalid Rasool; Rajput, Hafeez ur Rehman (Journal of Islamic and Religious Studies, 2022)
A transparent and unprejudiced system of accountability is a paramount importance to ensure proper functioning of the justice system. Undiscriminated justice system leads a nation to stability and prosperity and a flawed accountability system can cause the destruction of a nation. Presently, the lack of transparent and well-functioning accountability system is biggest hurdle in our way to achieve stable and progressive democracy. This article clarifies the need for accountability in the establishment of the welfare state and the process of accountability in the successful caliphate of Hazrat Umar. Historical research style has been adopted for research. It has been concluded through research that during the caliphate of Hazrat Umar Farooq R.A, the authorities were held accountable with the principles of courage and justice. Not only administrators but also the ruler himself whole heartedly and unquestionably presented himself before the law. His accountability system is a beacon of light for the present political system that could lighten path to a stable, and truly developed country. The research paper recommends that government ministers and other responsible persons should be held accountable if they are dishonest, bribe and misuse the public treasury. Eradication of corruption is possible only through a clear accountability process.